Investigation and Evaluation of the Healthy Risk of Heavy Metal Contents in Astragalus membranaceus of Shaanxi Province - Cai-xia Wang; Feng Liu; Yongbing Cheng; Lei Cao; Hua Wu (Journal of Food Protection, 2025)
Astragalus membranaceus is a widely used herbal medicine. This study was conducted to understand the heavy metal contents of A. membranaceus in Shaanxi Province of China and to evaluate the potential human health risks associated with its consumption. A total of 100 samples of A. membranaceus were collected during the harvest period in Shaanxi province. Inductively coupled plasma mass spectrometry (ICP-MS) was used to analyze cadmium (Cd), lead (Pb), nickel (Ni), total chromium (Cr), total arsenic (As), copper (Cu), cobalt (Co), selenium (Se), barium (Ba), molybdenum (Mo) in each sample, and the elements’ contents were evaluated. Total mercury(Hg) was measured using a direct mercury analyzer. The mean content of these elements in A. membranaceus was significantly different. All samples contained detectable concentrations of Cd, Pb, Ni, Cr, As, Cu, Co, Ba, and Mo. The concentrations of Hg and Se in certain specimens of A. membranaceus were found to be below the limits of detection. The contents of each element in all samples were lower than the legal limit published by the World Health Organization. Additionally, the contents of Cu, As, Hg, Cd, and Pb all conformed to the standards of the Pharmacopoeia of the People's Republic of China 2020. In this study, the target hazard quotient (THQ) for each metal and the hazard index (HI) through consumption of A. membranaceus were less than 1, indicating no significant noncarcinogenic risk associated with the consumption of A. membranaceus from the Shaanxi areas of China. The incremental lifetime cancer risk (ILCR) of each carcinogenic metal and the total carcinogenic risk (TCR) of all carcinogenic metals from A. membranaceus consumption for both adults and children were lower than the acceptable limit (ILCR and TCR = 10−4). This study used the total amount of elements for evaluation and did not consider the different forms of the elements in A. membranaceus. It also did not take into account the dissolution rate of heavy metals from A. membranaceus or the bioavailability of the elements. So this study employed a conservative evaluation method.